Ellsworth Kelly - portrait drawings - Carter, Jordan; Meyer, Richard 1966-; Salatino, Kevin 1956-; Tallman, Susan (The Art Institute of Chicago, 2023)
Featuring one hundred figurative works on paper by Ellsworth Kelly (1923-2015), this volume shows a new side of an artist best known for abstraction. These informal depictions of friends and expressive self-portraits -all rarely or never previously displayed or published- span the entirety of Kelly's career, from the mid-1940s to the early 2000s. Throughout his life, Kelly made portraits as a means of keeping his hand adept at drawing, which provided a place to test his ideas, refine his bold use of lines, and interrogate the space between naturalism and abstraction. These works also capture his social milieu, which intersected with other creative circles and the queer community. He painstakingly recorded how his own appearance changed over time, and once described some of these sketches by saying, "I use myself in order to draw." The accompanying critical essays unpack the ways in which such intimate efforts were fundamental to Kelly's practice and situate this important aspect of his work within the artist's wider oeuvre. Exhibition: Art Institute of Chicago, Chicago, USA (01.07-23.10.2023)
Rückseite Titelblatt: "Ellsworth Kelly: Portrait Drawings" was published in conjunction with an exhibition of the same title organized by the Art Institute of Chicago, from July 1 to October 23, 2023
Keywords: Kelly, Ellsworth -- 1923-2015; Zeichnung; Bildnis; Ausstellungskatalog -- Art Institute of Chicago -- 01.07.2023-23.10.2023 -- Chicago, Ill.; Bildband